PCSK6 is associated with handedness in individuals with dyslexia. - Scerri, T; Brandler, W; Paracchini, S; Morris, A; Ring, S; Richardson, A; Talcott, J; Stein, J; Monaco, A (Oxford University Press, 2011)
Approximately 90% of humans are right-handed. Handedness is a heritable trait, yet the genetic basis is not well understood. Here we report a genome-wide association study for a quantitative measure of relative hand skill in individuals with dyslexia [reading disability (RD)]. The most highly associated marker, rs11855415 (P = 4.7 × 10(-7)), is located within PCSK6. Two independent cohorts with RD show the same trend, with the minor allele conferring greater relative right-hand skill. Meta-analysis of all three RD samples is genome-wide significant (n = 744, P = 2.0 × 10(-8)). Conversely, in the general population (n = 2666), we observe a trend towards reduced laterality of hand skill for the minor allele (P = 0.0020). These results provide molecular evidence that cerebral asymmetry and dyslexia are linked. Furthermore, PCSK6 is a protease that cleaves the left-right axis determining protein NODAL. Functional studies of PCSK6 promise insights into mechanisms underlying cerebral lateralization and dyslexia.